Experimental determination of diagnostic window of cardiac troponins in the development of chronic anthracycline cardiotoxicity and estimation of its predictive value - Adamcova, Michaela; Lencova-Popelova, Olga; Jirkovsky, Eduard; Mazurova, Yvona; Palicka, Vladimir; Simko, Fedor; Gersl, Vladimir; Sterba, Martin (International journal of cardiology, 2015)
BACKGROUND: Cardiac troponins (cTns) seem to be more sensitive for the detection of anthracycline cardiotoxicity than the currently recommended method of monitoring LV systolic function. However, the optimal timing of blood sampling remains unknown. Hence, the aims of the present study were to determine the precise diagnostic window for cTns during the development of chronic anthracycline cardiotoxicity and to evaluate their predictive value. METHODS: Cardiotoxicity was induced in rabbits with daunorubicin (3mg/kg, weekly, for 8 weeks). Blood samples were collected 2-168 h after the 1st, 5th and 8th drug administrations, and concentrations of cTns were determined using highly sensitive assays: hs cTnT (Roche) and hs cTnI (Abbott). RESULTS: The plasma levels of cTns progressively increased with the rising number of chemotherapy cycles. While only a mild non-significant increase in both cTn levels occurred after the first daunorubicin dose, a significant rise was observed after the 5th and 8th administrations. Two hours after these administrations, a significant increase occurred with a peak between 4-6h and a decline until 24h. Discrete cTn release continued even after cessation of the therapy. While greater variability of cTn levels was observed around the peak concentrations, the values did not correspond well with the severity of LV systolic dysfunction. Unlike AMI in cardiotoxicity, cTn elevations may be better associated with cumulative dose and concentrations at steady state than cmax. CONCLUSIONS: To the best of our knowledge, this is the first study to precisely describe the diagnostic window and predictive value of cTns in anthracycline cardiotoxicity.
Keywords: kardiomyopatie; troponin T; Anthracyclines; Systole; Heart failure; echokardiografie; Daunorubicin; High sensitive troponin assay; Predictive Value of Tests; Echocardiography; Chemotherapy; Cardiomyopathy; Biomarkers; zvířata; daunomycin; Regression Analysis; Troponin I; antracykliny; biologické markery; Male; prediktivní hodnota testů; Heart; troponin I; Antibiotics, Antineoplastic; králíci; Cardiomyopathies; Troponin T; kardiotoxicita; systola; Animals; mužské pohlaví; Cardiotoxicity; Disease Models, Animal; Rabbits; regresní analýza; srdce; modely nemocí na zvířatech; protinádorová antibiotika